Deadly Disease vs. Chronic Illness: Competing Understandings of HIV in the HIV Non-Disclosure Debate - Speakman, Erica; Pawluch, Dorothy (Qualitative Sociology Review, 2021)
Over the past several decades, understandings of what it means to have contracted the human immunodeficiency virus (HIV) have shifted so that an infection once viewed as deadly and ultimately terminal is now largely regarded as chronic and manageable, at least in the West. Yet, the shift has not been complete. There are arenas of discourse where understandings of what health implications HIV carries with it are contested. One such space is the debate concerning the appropriate response to cases of HIV non-disclosure, that is, situations where individuals who are HIV-positive do not disclose their health status to intimate partners. This paper examines the competing constructions of HIV found within this debate, particularly as it has unfolded in Canada. Those who oppose the criminalization of non-disclosure tend to construct HIV as an infection that is chronic and manageable for those who have contracted it, not unlike diabetes. Those who support criminalization have mobilized a discourse that frames the infection as harmful and deadly. We use the case of the HIV non-disclosure debate to make the argument that representations of health conditions can become mired in larger social problems debates in ways that lead to contests over how to understand the fundamental nature of those conditions.